The Effect of Green Spinach Leaf Consumption on Hemoglobin Level Changes in Pregnant Women with Anemia - Indryani Indryani; Mustar Mustar; Hasnidar Hasnidar; Pattola Pattola; Artita arianti (Newinera Publisher, 2025)
Anemia has detrimental intergenerational consequences, including adverse pregnancy and birth outcomes, increased risks of mortality and morbidity, and impaired cognitive and motor development in children. These consequences, based on maternal status, indicate that anemia remains a major public health concern. This study aimed to analyze the effect of green spinach leaf vegetable consumption on changes in hemoglobin levels among pregnant women with anemia. A quasi-experimental study with a pretest-posttest group design was employed. The intervention involved administering 200 grams of green spinach vegetable daily for 7 days while temporarily discontinuing iron (Fe) tablet supplementation during the study period. The sampling technique used purposive sampling, involving 10 pregnant women diagnosed with anemia. The dependent variable was anemia, and the independent variable was the consumption of green spinach vegetables. Data were analyzed using the Shapiro-Wilk test and paired t-test to assess differences in hemoglobin levels before and after the intervention and to determine the effect of green spinach consumption on hemoglobin level changes in anemic pregnant women. The findings showed that the mean hemoglobin level before the intervention was 9.91 g/dL with a standard deviation of 0.612, which increased to a mean of 11.70 g/dL with a standard deviation of 0.878 after the intervention. The p-value was 0.000, which is less than 0.05, indicating a statistically significant increase in hemoglobin levels following the consumption of green spinach.